Magnetic Resonance Imaging Features of Normal Thyroid Parenchyma and Incidental Diffuse Thyroid Disease: A Single-Center Study - Kang, Taewoo; Kim, Dong Wook; Lee, Yoo Jin; Cho, Young Jun; Jung, Soo Jin; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Do Hun; Park, Ji Sun; Moon, Sung Ho; Ahn, Ki Jung; Baek, Hye Jin (Frontiers in Endocrinology, 2018)
Background: No previous studies have investigated the feasibility of magnetic resonance imaging (MRI) diagnosis for detecting incidental diffuse thyroid disease (DTD). This study investigated MRI features of normal thyroid parenchyma and incidental DTD. Methods: From January 2008 to December 2017, 387 patients underwent neck MRI in our hospital due to tumor/nodal staging (n = 137), lymphadenopathy (n = 122), inflammatory neck lesion (n = 85), congenital neck lesion (n = 12), and patient request (n = 31). Among them, 375 patients were excluded because of a lack of appropriate histopathological data on the thyroid parenchyma. Results: Among the patients included, 10 had normal thyroid parenchyma, 1 had Hashimoto thyroiditis, and 1 had diffuse hyperplasia. The common MRI features of normal thyroid parenchyma include iso-/slightly high and homogeneous signal intensity on T1/T2-weighted images, normal anteroposterior diameter of the thyroid gland, smooth margin, and homogeneously increased enhancement as compared to adjacent muscle. Hashimoto thyroiditis exhibited high and inhomogeneous signal intensity on T2-weighted images, while diffuse hyperplasia revealed an increased anteroposterior diameter and lobulated margin of the thyroid gland, and inhomogeneous enhancement. Conclusions: MRI may be helpful for detection of incidental DTD.